Taxonomic studies on the Neotropical Landrevinae with description of new taxa (Orthoptera, Grylloidea, Gryllidae) - De Campos, Lucas Denadai [UNESP]; De Mello, Francisco De A. G. [UNESP] (Magnolia Press, 2014)
The understanding of the subfamily Landrevinae has been modified by different authors since its creation. In the neotropics three genera are known to the present: Odontogryllus Saussure, 1877 (one from Mexico, the others amazonian), Brasilodontus de Mello, 1992 with two species (from Brazilian Atlantic Forest), e Valchica de Mello, 1992 with one species (from Costa Rica). De Mello (1992) erroneously created the tribe Odontogryllini for this cluster of neotropical genera, here suppressed. In the present paper we revise and add new species to Brasilodontus and describe two monotypic genera, Xulavuna n. gen. and Yarrubura, n. gen. An identification key to the genera of neotropical Landrevinae is presented as well as one for the species of Brasilodontus. The male fore wings of Xulavuna adenoptera n. sp. is remarkable regarding its shape and its glandular condition.
Keywords: Landrevinae; Orthoptera; glandular wing; description; new taxa; Neotropica